INTEGRATING MODIFIED LODGSERV WITH IMPROVEMENT GAP ANALYSIS TO DESIGN HOTEL SERVICE IMPROVEMENTS - Alfi Safrianti; Sugih Sudharma Tjandra (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The purpose of this study is to measure and analyze satisfaction of the Hotel X’s guests by its service quality. To achieve this, a modified LODGSERV scale is used as research instrument with total of 24 attributes used in questionnaire. In order to collect data, the questionnaire is distributed to guests who have stayed in Hotel X. The collected data is analyze using Improvement Gap Analysis to identify the highest priority level of the attributes that matter most to the hotel’s guest satisfaction. Based on the IGA matrix, there are 7 attributes that have the highest priority level for improvement. Furthermore, these attributes are identified by using fishbone diagram to obtain the root problem of each attribute. According to the root problems obtained, there are 15 suggestions for improvement are given to Hotel X.